EFEKTIVITAS PENERAPAN METODE BRAINSTRORMING DENGAN MEDIA POHON FISIKA UNTUK MELATIHKAN KEMAMPUAN BERPIKIR KREATIF SISWA SMP YLPI KELAS VIII - Umiliya, Umiliya; Nasir, Muhammad; Syafii, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study is to describe the improvement of student creative thinking abilities and the creativity of the eighth grade students of SMP YLPI Pekanbaru by using physics tree media in learning physics. The method used in this research is Quasi Experiment with Posttest-Only Design. This research was conducted in two classes that were given different treatments. The average results of the creative thinking ability of the experimental class students for each Individual is 72% with the medium category, while the average results of the creative thinking ability for each indicator is 73% with the medium category. The average results of student creativity questionnaires, for each individual in the experimental class by 70% in the medium category and the average results of each indicator by 73% also in the medium category. The average results of student creative thinking skills for each individual in the control class by 66% with medium categories and the average results of students creative thinking abilities for each indicator in the control class by 66% with medium categories. The average results of student creativity questionnaires in the Control class for each Individual by 66% in the medium category and the average results of student creativity questionnaires for each indicator 67% also in the medium category. The results of this study can be concluded that the use of Physics tree media in Physics learning can increase the creativity of eighth grade students of SMP YLPI Pekanbaru. The recommendation of this study is the learning process carried out over a long period of time, because it takes a long time to increase student creativity.Key Words: Effectiveness, Brainstroming, Physics Tree Media